(untitled) (Praxis Educativa, 2017)
This article is the result of a research aimed to analyze the results achieved by students of public and private secondary schools in the application of the external test known as Saber 11 during 2011, 2012 and 2013, in order to determine how, on the basis of these results, the Ministry of National Education and the media has established a marked discrimination between public and private education in terms of educational quality